A Single Complex Agpat2 Allele in a Patient With Partial Lipodystrophy - Broekema, Marjoleine F.; Massink, Maarten P. G.; De Ligt, Joep; Stigter, Edwin C. A.; Monajemi, Houshang; De Ridder, Jeroen; Burgering, Boudewijn M. T.; van Haaften, Gijs W.; Kalkhoven, Eric (Frontiers in Physiology, 2018)
Genetic lipodystrophies are a group of rare syndromes associated with major metabolic complications - including severe insulin resistance, type 2 diabetes mellitus, and hypertriglyceridemia - which are classified according to the distribution of adipose tissue. Lipodystrophies can be present at birth or develop during life and can range from local to partial and general. With at least 18 different genes implicated so far, definite diagnosis can be challenging due to clinical and genetic heterogeneity. In an adult female patient with clinical and metabolic features of partial lipodystrophy we identified via whole genome sequencing a single complex AGPAT2 allele [V67M;V167A], functionally equivalent to heterozygosity. AGPAT2 encodes for an acyltransferase implicated in the biosynthesis of triacylglycerol and glycerophospholipids. So far homozygous and compound heterozygous mutations in AGPAT2 have only been associated with generalized lipodystrophy. A SNP risk score analysis indicated that the index patient is not predisposed to lipodystrophy based on her genetic background. The partial phenotype in our patient is therefore more likely associated to the genetic variants in AGPAT2. To test whether the resulting double-mutant AGPAT2 protein is functional we analysed its in vitro enzymatic activity via mass spectrometry. The resulting AGPAT2 double mutant is enzymatically inactive. Our data support the view that the current classification of lipodystrophies as strictly local, partial or generalized may have to be re-evaluated and viewed more as a continuum, both in terms of clinical presentation and underlying genetic causes. Better molecular understanding of lipodystrophies may lead to new therapies to treat adipose tissue dysfunction in common and rare diseases.